1999
DOI: 10.1021/la990300y
|View full text |Cite
|
Sign up to set email alerts
|

New Catanionic Glycolipids. 1. Synthesis, Characterization, and Biological Activity of Double-Chain and Gemini Catanionic Analogues of Galactosylceramide (galβ1cer)

Abstract: New double-chain and gemini catanionic analogues of the glycolipid galβ1ceridentified as a cell receptor of the HIV-1 viruswere easily prepared in two steps from unprotected lactose. Due to their sugar moiety, these new catanionic surfactants were able to be cationized by sodium ions and therefore to be characterized in their monomeric forms by electrospray mass spectrometry. To our knowledge, this is the first time that catanionic surfactants have been directly observed, proving undoubtedly their existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 31 publications
4
85
0
3
Order By: Relevance
“…In order to confi rm the complex formation between the cationic species and the alkyl dicarboxylic acid compounds, nano-ESI-MS and 1 H-NMR spectroscopy measurements were performed at a fi xed Xc 0.33. Similar ESI-MS analyses have been reported by Blanzat et al, where the stoichiometric complex formation was suggested to have occurred for the mixture of alkylamine and alkyl dicarboxylic acid compounds 12 . Nano-ESI-MS spectra are shown in Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In order to confi rm the complex formation between the cationic species and the alkyl dicarboxylic acid compounds, nano-ESI-MS and 1 H-NMR spectroscopy measurements were performed at a fi xed Xc 0.33. Similar ESI-MS analyses have been reported by Blanzat et al, where the stoichiometric complex formation was suggested to have occurred for the mixture of alkylamine and alkyl dicarboxylic acid compounds 12 . Nano-ESI-MS spectra are shown in Fig.…”
Section: Resultssupporting
confidence: 86%
“…A similar concept has been reported previously 12 14 . For example, it has been suggested that an alkylamine compound with sugar moieties forms a stoichiometric complex with alkyl dicarboxylic acid when mixed at a molar ratio of 2:1 in aqueous solutions 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation methods produce IPAs as precipitates by mixing equimolar amounts of oppositely charged surfactants in water and removing the residual counterions by repeated washing and centrifugation 12,57 . Subsequently, elemental analysis is usually performed to confirm that the IPA is composed of two oppositely charged moieties of mixed cationic/anionic surfactants at an equimolar ratio 12,58 .…”
Section: Ipasmentioning
confidence: 99%
“…In unserer Arbeitsgruppe wurden ebenfalls verschiedenartige wasserlösliche katanionische Tenside hergestellt, [109,110,[114][115][116] …”
Section: Niosome 331 Struktur Und Eigenschaftenunclassified